Preparation and X-ray structure of 2-iodoxybenzenesulfonic acid (IBS) – a powerful hypervalent iodine(V) oxidant - Mironova, Irina A.; Postnikov, Pavel S.; Yusubova, Rosa Y.; Yoshimura, Akira; Wirth, Thomas; Zhdankin, Viktor V.; Nemykin, Victor N.; Yusubov, Mekhman S. (Beilstein Journal of Organic Chemistry, 2018)
The selective preparation of 2-iodoxybenzenesulfonic acid (IBS, as potassium or sodium salts) by oxidation of sodium 2-iodobenzenesulfonate with Oxone or sodium periodate in water is reported. The single crystal X-ray diffraction analysis reveals a complex polymeric structure consisting of three units of IBS as potassium salt and one unit of 2-iodoxybenzenesulfonic acid linked together by relatively strong I=O···I intermolecular interactions. Furthermore, a new method for the preparation of the reduced form of IBS, 2-iodosylbenzenesulfonic acid, by using periodic acid as an oxidant, has been developed. It has been demonstrated that the oxidation of free 2-iodobenzenesulfonic acid under acidic conditions affords an iodine(III) heterocycle (2-iodosylbenzenesulfonic acid), while the oxidation of sodium 2-iodobenzenesulfonate in neutral aqueous solution gives the iodine(V) products.
Keywords: hypervalent iodine; iodine; 2-iodoxybenzenesulfonic acid; oxidation; X-ray

Hypervalent Iodine Chemistry - Wirth, T. (Springer, 2016)

Hypervalent Iodine Chemistry - Zhdankin, V. V. (Wiley, 2014)

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

(untitled) - Morimoto, K.; Dohi, T.; Kita, Y. (Synlett, 2017)

(untitled) - Yoshimura, A.; Yusubov, M. S.; Zhdankin, V. V. (Org. Biomol. Chem., 2016)

(untitled) - Silva, J. L. F.; Olofsson, B. (Nat. Prod. Rep., 2011)

(untitled) - Zhdankin, V. V.; Muñiz, K. (J. Org. Chem., 2017)

(untitled) - Konovalov, A. I.; Antipin, I. S.; Burilov, V. A.; Madzhidov, T. I.; Kurbangalieva, A. R.; Nemtarev, A. V.; Solovieva, S. E.; Stoikov, I. I.; Mamedov, V. A.; Zakharova, L. Y.; Gavrilova, E. L.; Sinyashin, O. G.; et al. (Russ. J. Org. Chem., 2018)

(untitled) - Duschek, A.; Kirsch, S. F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Zhdankin, V. V. (J. Org. Chem., 2011)

(untitled) - Satam, V.; Harad, A.; Rajule, R.; Pati, H. (Tetrahedron, 2010)

(untitled) - Uyanik, M.; Ishihara, K. (Aldrichimica Acta, 2010)

(untitled) - Uyanik, M.; Akakura, M.; Ishihara, K. (J. Am. Chem. Soc., 2009)

(untitled) - Cui, L.-Q.; Liu, K.; Zhang, C. (Org. Biomol. Chem., 2011)

(untitled) - Uyanik, M.; Mutsuga, T.; Ishihara, K. (Molecules, 2012)

(untitled) - Uyanik, M.; Ishihara, K.; Zhang, C.; Cui, L.-Q. (e-EROS Encycl. Reagents Org. Synth., 2012)

(untitled) - Uyanik, M.; Mutsuga, T.; Ishihara, K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Koposov, A. Y.; Litvinov, D. N.; Zhdankin, V. V.; Ferguson, M. J.; McDonald, R.; Tykwinski, R. R. (Eur. J. Org. Chem., 2006)

(untitled) - Kraszkiewicz, L.; Skulski, L. (ARKIVOC, 2003)

(untitled) - Kazmierczak, P.; Skulski, L.; Kraszkiewicz, L. (Molecules, 2001)

(untitled) - Moss, R. A.; Bose, S.; Krogh-Jespersen, K. (J. Phys. Org. Chem., 1997)

(untitled) - Koser, G. F.; Sun, G.; Porter, C. W.; Youngs, W. J. (J. Org. Chem., 1993)

(untitled) - Koposov, A. Y.; Karimov, R. R.; Pronin, A. A.; Skrupskaya, T.; Yusubov, M. S.; Zhdankin, V. V. (J. Org. Chem., 2006)